Exploring The Impact Of Green Finance, Financial Literacy, And Social Capital On The Performance And Financial Sustainability Of Indonesian MSMEs - Efriyani Sumastuti; Subur Harahap; Godlif Sianipar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The long-term survivability and financial performance of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia are examined in this study in relation to social capital, financial literacy, and green finance. A quantitative approach that blended structural equation modeling (SEM) and partial least squares (PLS) regression analysis was used to examine survey data collected from a sample of 267 MSMEs. The study found that sustainability, social capital, financial literacy, and green finance are strongly correlated with the financial success of MSMEs. It was shown that MSME performance and sustainability were specifically enhanced by social capital, financial literacy, and green finance. The findings emphasize how important it is to integrate sustainable practices, raise financial literacy, and foster social networks within Indonesia's MSME sector in order to promote inclusive growth and sustainable development